Altered dendritic morphology of MEC II pyramidal and stellate cells in Rett syndrome mice - Krishnan, Manigandan; Mydeen, Ayishal B.; Nakhal, Mohammed M.; Ibrahim, Marwa F.; Jayaraj, Richard L.; Ljubisavljevic, Milos R.; Hamad, Mohammad I. K.; Ismail, Fatima Y. (Frontiers in Neuroanatomy, 2025)
IntroductionMutations in the methyl-CpG-binding protein-2 gene (MECP2), which cause Rett syndrome (RTT), disrupt neuronal activity; however, the impact of the MECP2 loss-of-function on the cytoarchitecture of medial entorhinal cortex layer II (MECII) neurons—crucial for spatial memory and learning—remains poorly understood.MethodsIn this study, we utilized Golgi staining and neuron tracing in the Mecp2+/− mouse model of RTT to investigate the pyramidal and stellate cell alterations in MECII.Results and discussionOur findings revealed that pyramidal cells displayed a significant reduction in apical dendritic length, soma size, and spine density, while basal dendrites showed increased dendritic complexity and branching. On the other hand, stellate cells exhibited dendritic hypertrophy along with increased soma size, primary dendrites, and localized increase in dendritic intersections, despite an overall reduction in total dendritic length and spine density. These findings underscore the notion that MECP2 loss-of-function can disrupt MECII pyramidal and stellate cell cytoarchitecture in a cell-type-specific manner, emphasizing its critical role in maintaining proper dendritic morphology in circuits, which is crucial for learning and memory.